F Formulasi Dan Evaluasi Sediaan Essence Ekstrak Daun Sirih Hijau (Piper Betle L.) Sebagai Anti Jerawat: Formulasi Dan Evaluasi Sediaan Essence Ekstrak Daun Sirih Hijau (Piper Betle L.) Sebagai Anti Jerawat - Dewi, Sinta; Malahayati, Siti; Darsono, Putri Vidiasari (Jurnal Pelayanan Kefarmasian dan Sains, 2023)
Background: Piper betel leaf extract has antibacterial activity against P.acnes because it contains tannins, flavonoids, alkaloids, and terpenoid compounds. Objective: The purpose of this study is to formulate piper betel leaf extract in the form  of essence that meets the requirements of physical quality and has antibacterial activity against P.acnes. Methods:  This study uses true experimental method  and well diffusion method for antibacterial test. The essence preparation was  made with 3 different extract concentrations (concentrations of 5%, 10%, and 20%), then a physical evaluation was carried out and then the formulation was tested for antibacterial activity against P.acnes. The data obtained were statistically analyzed ANOVA with a significance value of 0.05. Results: The results showed that  the essence preparation  had a yellowish-brown to dark brown color, liquid form and characteristic smell of betel leaves with a pH of 5.4-5.5, homogeneous preparation, viscosity 324-463, dispersion power 9.74 mm-11.62mm, and in antibacterial activity tests showed the ability to inhibit the growth of P.acnes bacteria  by having inhibitory power that was categorized as strong. Conclusion: The results of the physical evaluation and the results of the antibacterial activity test for essence preparations had a significant effect on variations in extract concentrations because the p-value was <0.05. Based on the evaluation results, all formulas met the specifications, and the most optimal was formula II